Causes and solutions for the stagnation of Islamic banking in Turkey. Issue 1 (10th July 2017) - Yanīkkaya, Halit; Pabuçcu, Yaşar Uğur
Abstract : Purpose: This paper aims to evaluate the root causes of stagnation of the Islamic banking sector in Turkey in three steps and proposes solutions and policy recommendations. Design/methodology/approach: First, global Islamic banking practices in terms of governance and instruments are summarised and compared with the Turkish experience. Second, the financial and efficiency ratios of Turkish Islamic banks (IBs) and conventional banks (CBs) are compared and analysed for the period 2005 to 2015. Finally, the long-term growth strategy of Turkish IBs is evaluated. Findings: This paper asserts that Islamic banking in Turkey diverges from Islamic banking practices of prominent countries by not having a Sharīʿah governance framework at either a national or bank level. Turkey is thus immediately in need of a sound Sharīʿah governance framework. Increasing the variety of instruments and improving the perception of Islamic banking in the society are other critical points. Furthermore, regulatory and research institutions specifically focusing on Islamic banking are insufficient. A large number of financial and efficiency ratios reveal that the efficiency and profitability of IBs fall behind that of CBs. IBs should improve their business models, operational efficiencies and information technology infrastructure as these issues are undervalued in their growth strategy. Originality/value: This study sheds light on the Turkish Islamic banking sector, which is a rarely studied topic. It is the first study that provides institutional differences of banking practices and evaluates the efficiency status and growth strategy of IBs in Turkey.